2021
DOI: 10.1097/aud.0000000000000992
|View full text |Cite
|
Sign up to set email alerts
|

Self-report Measures of Hearing and Vision in Older Adults Participating in the Canadian Longitudinal Study of Aging are Explained by Behavioral Sensory Measures, Demographic, and Social Factors

Abstract: The authors had full editorial control over the design and reporting of the present research using CLSA data. The opinions expressed in this manuscript are the authors' own and do not reflect the views of the CLSA. The authors thank Biljana J. Stojkova for help with the multiple imputation analyses, and Dawn Guthrie for contributions to the earlystage planning of the project. Author contributions: A.H. designed and performed the data analyses and wrote the paper. M.K.P.-F., W.W., N.P. and P.M. conceived of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 114 publications
9
19
1
Order By: Relevance
“…We also found that older adults were less likely than middle-aged adults to report hearing difficulties. This finding is in line with studies suggesting that as people get older, they report fewer hearing issues (e.g., Hämäläinen et al 2021; Kamil et al 2015; Tsimpida et al 2020). Many hypotheses have been postulated to explain this phenomenon.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that older adults were less likely than middle-aged adults to report hearing difficulties. This finding is in line with studies suggesting that as people get older, they report fewer hearing issues (e.g., Hämäläinen et al 2021; Kamil et al 2015; Tsimpida et al 2020). Many hypotheses have been postulated to explain this phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…In the same way, Kamil et al (2015) have observed that the association between self-reported measures of hearing and hearing thresholds differs across biological sex, age, race/ethnicity, and education. More recently, Hämäläinen et al (2021) analyzed the baseline data of the cohort of the Canadian Longitudinal Study on Aging and found that young adult males, and individuals with more comorbid health conditions were significantly more likely to self-report sensory difficulty (vision and hearing impairment). Overall, the evidence suggested that age, sex, mental and physical health, and education may be important moderator variables when considering the relationship between hearing loss and cognition.…”
Section: Hypothesis For the Mixed Findings In The Relationship Betwee...mentioning
confidence: 99%
“…A number of studies have shown age effects potentially related to how one’s perspective on the degree of reported HD changes over the lifetime compared with changes in auditory thresholds, but the results of such studies are not always in agreement. Some studies have shown that younger adults underestimate their hearing abilities while older adults are better estimators of their audiometric thresholds, but can also overestimate their abilities (Kamil et al 2015; Oosterloo et al 2020; Hämäläinen et al 2021), yet others have shown that older adults with normal hearing thresholds report more disability hearing in difficult situations than younger adults (Banh et al 2012; Gatehouse & Noble 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] There are also variables that were not included in these analyses that may influence subjective assessments of hearing status, such as the degree of asymmetry, vision, and other comorbidities, and is an area of needed research. 35,[40][41][42][43] The generalizability of the cohort to the older adult population of the United States is also limited, as the participants from the four US communities were lacking in racial and ethnic minority representation beyond African American participants. In addition, given that ARIC participants needed to survive and be healthy enough to attend visit 6, they likely do not represent many older adults in the general US population, particularly those with cognitive impairment, and so our results may also not be generalizable to those individuals.…”
Section: Discussionmentioning
confidence: 99%